Relationship between urinary levels of organophosphate metabolites and pesticide exposures among rural school boys of the Western Cape - Molomo, Ntsubise Regina (Department of Public Health and Family Medicine, 2021)
Background: Biomonitoring of pesticides is an objective measure of short-term pesticide exposure as it measures possible exposure in the human body. Current evidence on the relationship between demographic, socio-economic and pesticide exposure risk factors and urinary levels of organophosphate (OP) pesticide metabolites among children is generally incomplete and conflicting in some cases. There is therefore a need for further research. Objectives: This study investigated the relationship between socio-economic, demographic and reported pesticide exposure related activities and characteristics in relation to urinary levels of three dialkyl phosphate (DAP) metabolites (diethyl phosphate (DEP), dimethyl phosphate (DMP) and dimethyl triphosphate (DMTP)) among boys living in the rural areas of the Western Cape, South Africa. Methods: This was an analysis of data collected during a cross- sectional study of 183 boys from three agricultural intense areas in the Western Cape of South Africa between April 2007 and March 2008. Measurements included a questionnaire on demographic, socio-economic and pesticide exposure risk factors and analysis of spot urine samples for DAP metabolites. Results: Most of the boys (70%) lived on farms with a median age of 12 years (range: 5.0 - 19.5 years). The median concentrations of DAP, DEP, DMP and DMTP were 68.3 ng/ml (IQR= 27.9; 129.5), 5.5 ng/ml, 32.6 ng/ml and 16.7 ng/ml, respectively. The sum of the three DAP levels wasinversely associated with age. Children older than 14 years had less DAP levels (β = -68.1; 95% CI: -136.8,0.6) than children 9 years and younger. DAP levels also varied significantly with residential area, with the levels highest in Grabouw (apple farming), followed by Hex River Valley (grape farming) (β= -52.1; 95% CI: -97.9, -6.3) then Piketberg (wheat farming) (β= -54.2; 95% CI:-98.8, -9.7). Other weaker and non-significant associations with increased DAP levels were found with increased household income, member of household work with pesticides, living on a farm, drinking water from an open water source and eating crops from the vineyard and or garden. Conclusion: The study found younger age and living in and around an apple and grape farms, to be associated with increased urinary DAP concentrations among the school children provide evidence that younger age and residential area can be associated with increased urinary DAP concentrations among boys. Additionally, there are other household and behavioural characteristics that are associated with elevated urinary DAP levels. Further studies with larger sample sizes and longitudinal designs to improve the statistical power and the associations found are recommended. The study provided more insight to incomplete and inconclusive evidence of previous studies.